1955
DOI: 10.3181/00379727-88-21640
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Colonial Variants of Brucellae in vivo

Abstract: illthough recent studies have demonstrated the mutational character of dissociation (1) and the selective role of metabolites on population changes in synthetic broth cultures of brucellae( 2.3) information on population changes in infected animals is fragmentary. Most investigations on the establishment of colonial variants in animal tissues have been with animals inoculated with variants isolated from stock cultures either alone or in combination with smooth (S) brucellae(4-7). These experiments demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1956
1956
1981
1981

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The unaltered smooth selective capacity of fibroblasts cultured in antiserum (lacking in SS factor), indicates one reason why animals lacking the SS factor, and even immune animals, clear non-smooth brucellae from their body much more rapidly than they do the smooth type ( 14).…”
Section: M and R Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unaltered smooth selective capacity of fibroblasts cultured in antiserum (lacking in SS factor), indicates one reason why animals lacking the SS factor, and even immune animals, clear non-smooth brucellae from their body much more rapidly than they do the smooth type ( 14).…”
Section: M and R Variantsmentioning
confidence: 99%
“…Thus, they have been generally considered to be of little significance in brucellosis. However, several instances of mutation from smooth to mucoid in vivo have recently been demonstrated, in which the mucoid variants were recovered as often from unabscessed as from abscessed tissue ( 14) .…”
mentioning
confidence: 99%
“…Recovery of approximately equal numbers of all three colonial types from infected hamster blood may reflect selection of mutants or an equilibration process. The establishment of colonial variants of brucellae in vivo has been reported by Berman, Redfearn, and Simon (1955), who suggested that local accumulations of metabolites may favor the establishment of variants. The role of immunity in the selection of colonial variant brucellae was studied by Redfearn, Simon, and Berman (1956).…”
Section: Discussionmentioning
confidence: 85%